The royal saints of Anglo-Saxon England a study of West Saxon and East Anglian cults - Ridyard, Susan J. (Cambridge Cambridge University Press, 1988)
Within Anglo-Saxon England there was a strong and enduring tradition of royal sanctity - of men and women of royal birth who, in an age before the development of papal canonisation, came to be venerated as saints by the regional church. This study, which focuses on some of the best-documented cults of the ancient kingdoms of Wessex and East Anglia, is a contribution towards understanding the growth and continuing importance of England's royal cults. The author examines contemporary and near-contemporary theoretical interpretations of the relationship between royal birth and sanctity, analyses in depth the historical process of cult-creation, and addresses the problem of continuity of cult in the aftermath of the Norman Conquest of 1066. An understanding therefore emerges of the place of the English royal saint not only in Anglo-Saxon society but also in that of the Anglo-Norman realm.
Appendix1: The life of St. Edburga of Winchester / by Osbert of Clare, Prior of Westminster: p.253-308
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Christian saints -- Cult -- England -- History, Middle Ages, 600-1500.; Monarchy -- England -- History, To 1500.; Anglo-Saxons -- Kings and rulers; Princesses -- Great Britain; Princes -- Great Britain; Anglo-Saxons -- Kings and rulers; Princesses -- Great Britain; Princes -- Great Britain; Monarchy -- England -- History -- To 1500; Christian saints -- Cult -- England -- History -- Middle Ages, 600-1500; Christian saints ; Cult ; England ; History ; Middle Ages, 600-1500; Monarchy ; England ; History ; To 1500; Anglo-Saxons ; Kings and rulers; Princesses ; Great Britain; Princes ; Great Britain; England ; Church history ; 449-1066; England -- Church history, 449-1066.; England -- Church history -- 449-1066